False working memories? Semantic distortion in a mere 4 seconds - Atkins, Alexandra S.; Reuter-Lorenz, Patricia A. (Memory & cognition, 2008)
False memories are well-established, episodic memory phenomena: Semantically related associates are confidently and erroneously remembered as studied items. We report four experiments yielding similar effects in a working memory paradigm. Four semantically related words were retained over a brief interval. Whether or not the interval was filled with a math verification task, semantically related lures were mistakenly recognized as members of the memory set and took longer to reject than did unrelated negative probes. In a short-term recall task, semantic intrusions exceeded other errors (e.g., phonemic). Our results demonstrate false memory effects for a subspan list when a mere 4 sec was given between study and test. Such rapid semantic errors presumably result from associative processing, may be related to familiarity-based proactive interference in working memory, and are consistent with recent models that integrate short- and long-term memory processes.